Pre-eclampsia and cardiovascular risk: a long-term nationwide cohort study on over 120 000 Finnish women - Mika Gissler; Hanna Savolainen-Peltonen; Olavi Ylikorkala; Johanna Joensuu; Minttu Venetkoski; Tomi Sakari Mikkola (BMJ Open)
Objectives To investigate the impact of pre-eclampsia on the future cardiovascular risk in Finnish womenDesign A registry-based nationwide controlled cohort study.Setting Women hospitalised for pre-eclampsia in 1969–1993 and control women with a history of normotensive pregnancies followed from the pre-eclampsia diagnosis until 2019 for cardiovascular outcomes.Participants 31 688 women with and 91 726 control women without a history of pre-eclampsia.Primary outcome measures Incidences of and deaths from ischaemic heart disease (IHD), myocardial infarction (MI) and stroke.Results In total, 25 813 (81.5%) women had pre-eclampsia without severe features, 4867 (15.4%) had pre-eclampsia with severe features and 1006 (3.2%) women developed eclampsia. Women with a history of pre-eclampsia showed elevated risks for IHD (HR 1.52, 95% CI 1.44 to 1.59), MI (HR 1.66, 95% CI 1.52 to 1.81) and stroke (HR 1.40, 95% CI 1.32 to 1.48). The risks for death from IHD (HR 1.50, 95% CI 1.28 to 1.75), MI (1.63, 95% CI 1.30 to 2.05) and stroke (1.44, 95% CI 1.03 to 2.01) were also elevated. Pre-eclampsia with severe features or eclampsia was accompanied with 15% higher IHD risk, 19% higher MI risk and 26% higher stroke risk than pre-eclampsia without severe features. The highest risk elevations of 30% for IHD, 32% for MI and 30% for stroke were observed in women with recurrent pre-eclampsia (n=4180).Conclusion Pre-eclampsia-related significant elevations in CVD risks of Finnish women with inherently high risk for these diseases were of the same magnitude as reported previously from other countries. Thus, women with a history of pre-eclampsia should be screened and treated early for modifiable cardiovascular risk factors.